2005
DOI: 10.12968/jowc.2005.14.1.26723
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for venous ulcer healing in a non-selected population of ambulatory patients

Abstract: Clinical indicators such as simple ulcer length measurement and ulcer duration may help physicians to detect patients with a prognosis of poor healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 9 publications
4
54
0
Order By: Relevance
“…Also, it remains unclear whether demographic characteristics of VLU patients or their co-morbidities are really associated with impaired healing. Some studies demonstrated a delayed healing in elderly patients [12,16,18,26] while others found a better healing in this age group [19] or no association of the age with healing [8,10,13]. In one study the patients aged less than 40 years were more likely to have VLUs healed in a short time [15].…”
Section: Risk Factors Related To the Patientmentioning
confidence: 98%
See 4 more Smart Citations
“…Also, it remains unclear whether demographic characteristics of VLU patients or their co-morbidities are really associated with impaired healing. Some studies demonstrated a delayed healing in elderly patients [12,16,18,26] while others found a better healing in this age group [19] or no association of the age with healing [8,10,13]. In one study the patients aged less than 40 years were more likely to have VLUs healed in a short time [15].…”
Section: Risk Factors Related To the Patientmentioning
confidence: 98%
“…Most of these studies gave a concise picture. Parameters predicting poor outcome comprise large ulcer size [5][6][7][8][9][10][11][12][13][14][15][16][17] and long ulcer duration [5, 6, 8-10, 12-16, 18, 19]. However, the cutoff values of the size and duration varied between the studies, probably because of different cohorts assessed (for example: all VLU patients in the community, only selected patients, those included into the clinical trials).…”
Section: Risk Factors Related To the Ulcermentioning
confidence: 99%
See 3 more Smart Citations